Sago Supports Food Security Dealing with the Impact of Climate Change - JANES BERTHY ALFONS (Puslitbang Perkebunan, 2011)
Sago (Metroxylon spp.) is one source of traditional foods potentially to be developed to support local and national food security. Nutritional value of sago is almost equal to other food sources, such as rice, maize, cassava, and potato. The potential area of sago in Moluccas is large enough. In addition, its production potential in the region is high enough (30 t/ha/yr), far exceeding other sources of food (rice, corn, and potato). Sago flour and its processed products can be classified as functional foods because it has high carbohydrate content (84.7%) and dietary fibre (3.69 to 5.96%), low glycemic index (28), resistant starch, non-starch polysaccharide, and short chain carbohydrates that are very useful for health. In the sago farming, from the sago cultivation (pre-harvest) until the wet sago flour processing (post-harvest) is done naturally, hence, the sago starch can be categorized as 100% organic food. Wet sago starch can be dried to increase the storage durability and the packaging attractiveness. Moreover, the flour can be processed into a variety of cakes and pastries. The strategy taken in the development efforts of sago as a component of local and national food security needs to be done starting from up-stream to down-stream, including technical and management aspects by developing a competitive, pro-poor, sustainable, and decentralized sago agribusiness. In order to strengthen the food security, utilization of the sago as a component of food security should consider the following matters: (1) diversification of sago processed products should be diverse, nutritious, and balanced, (2) maintain and improve consumption patterns of the sago-based foods, (3 ) quality and food safety to be guaranteed, (4) use of appropriate technology, and (5) efforts increase added value through improving and increasing highly competitive sago-based products. Key words: Sago, traditional food, functional food, organic food, food security.